2019
DOI: 10.1016/j.clnu.2018.05.024
|View full text |Cite
|
Sign up to set email alerts
|

ESPEN guideline on clinical nutrition and hydration in geriatrics

Abstract: A range of effective interventions is available to support adequate nutrition and hydration in older persons in order to maintain or improve nutritional status and improve clinical course and quality of life. These interventions should be implemented in clinical practice and routinely used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
1,115
2
143

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 980 publications
(1,283 citation statements)
references
References 307 publications
(382 reference statements)
23
1,115
2
143
Order By: Relevance
“…A study by Cluskey and Kim undertaken in the USA suggested that finger foods are judged by healthcare professionals, working in long‐term care settings, as being beneficial for residents, cheap and easily implemented in institutions. The limited adverse effects and expense to provide these types of foods means that their use continues to remain in clinical guidelines on nutrition and hydration in geriatrics .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study by Cluskey and Kim undertaken in the USA suggested that finger foods are judged by healthcare professionals, working in long‐term care settings, as being beneficial for residents, cheap and easily implemented in institutions. The limited adverse effects and expense to provide these types of foods means that their use continues to remain in clinical guidelines on nutrition and hydration in geriatrics .…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, relatives of older people frequently report an inadequate amount of appropriate food and lack of support for people unable to feed themselves . The European Society for Clinical Nutrition and Metabolism (ESPEN) clinical recommendations suggest using finger foods for older adults because of their limited cost and low risk, although the supporting evidence for this intervention is sparse.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These varying prevalence rates can be explained by the different available definitions, screening instruments, spectrum of patients and settings. Well‐known risk factors for malnutrition are forms of cancer, digestive system diseases, loss of appetite, restrictive diets, reduced mobility, comorbidity, higher dependency levels during daily activities, increased age or pain (Raynaud‐Simon, Revel‐Delhom, & Hébuterne, ; Volkert et al, ). According to Meier and Stratton () psychosocial factors or diseases, including dementia, anxiety and depression, can also contribute to lower food intake.…”
Section: Introductionmentioning
confidence: 99%